Design of a Warehouse Inventory Management System Using FEFO Method in NUSA Niaga Multi-Tenant - Lina Nur Afifah; Aulia Hamdi; Sri Rahayu; Intan Nur Sifa; Rizki Cahya Putri; Purnia Setiawati; Aulia Suryaning Tyas; Mayza Nurul Khasanatun Nisa (Yayasan Kita Menulis, 2026)
Most village-based businesses still manage their inventory manually, from monitoring warehouse stock and generating reports and checking items based on expiration dates. This process is considered inefficient and carries the risk of errors in data recording and reporting. In the process of transferring inventory to the display on the web-based NUSA Niaga platform, the FEFO method is applied. Needs analysis, system design, design implementation, and system documentation were conducted. Literature review on management systems, the FEFO method, multi-tenant architecture, and RBAC were used for data collection. The system was designed to monitor inventory, manage products nearing expiration, record goods transfers, and implement multi-tenant functionality using flowcharts, ERDs, and DFDs. This system is expected to help manage BUMDes warehouse in a more connected and structured manner.